Development of a Linktree-Based E-Module for Enhancing Fifth Graders' Reading Skills in Narrative Texts - Fariha, Ernisa; Sismulyasih, Nugraheti; Purwati, Panca Dewi (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2024)
The use of teaching materials plays a crucial role in improving learning quality. Uninteresting materials can lead to a lack of enthusiasm and difficulty in understanding the content. This research aims to develop a Linktree-based E-Module for Indonesian language learning to help students extract important information from narrative texts and improve their reading skills at SD Negeri Batealit 01. The study employs the Research and Development (R&D) method using the Borg and Gall development model. The subjects of this research were fifth-grade teachers and students at SD Negeri Batealit 01. Data collection methods included interviews, documentation, field observations, and questionnaires on teacher and student needs. Data analysis techniques involved feasibility and effectiveness tests of the E-Module. Results from the feasibility tests by material and media experts showed scores of 87.5% and 90%, respectively, both in the very feasible category. The N-Gain test results before and after learning showed a result of 0.6217, categorized as medium, indicating effective use as a learning medium. The conclusion of this research is that the Linktree-based E-Module is both feasible and effective for use in the learning process. It enhances understanding of extracting important information from narrative texts. It is hoped that using Linktree-based E-Modules can increase students' motivation and critical thinking skills.